Idiopathic Ninth, Tenth, and Twelfth Cranial Nerve Palsy with Ipsilateral Headache: A Case Report - Sun Seung-Ho (Korean Pharmacopuncture Institute, 2012)
Objective: This case report is to report the effect of Korean traditional treatment for idiopathic ninth, tenth, and twelfth cranial nerve palsy with ipsilateral headache. Methods: The medical history and imaging and laboratory test of a 39-year-old man with cranial palsy were tested to identify the cause of disease. A 0.2-mL dosage of Hwangyeonhaedoktang pharmacopuncture was administered at CV23 and CV17, respectively. Acupuncture was applied at P06, Li05, TE05, and G37 on the right side of the body. Zhuapiandutongbang (左偏頭痛方) was administered at 30 minutes to 1 hour after mealtime three times a day. The symptoms were investigated using Visual Analogue Scale (VAS). Results: The results of magnetic resonance imaging (MRI), computed tomography (CT), and laboratory tests were normal. The medical history showed no trauma, other illnesses, family history of diseases, medications, smoking, drinking and so on. All symptoms disappeared at the 10th day of treatment. Conclusion: Korean traditional treatment such as acupuncture, pharmcopuncture, and herbal medicine for the treatment of ninth, tenth, and twelfth cranial nerve palsy of unknown origin is suggested to be effective even though this conclusion is based on a single.